Hydrographic Data Fulfillment Strategy to Improve the Capabilities of Pushidrosal as a National Hydrographic Institution in order to Answer the Mandatory Imo Member States Audit Scheme (MIMSAS) - Khoirul Anwar; Edi Iwan Bangun; Dany Wira Nugraha (Journal Research of Social Science, Economics, and Management, 2025)
Indonesia, as the largest archipelagic state, plays a critical role in global maritime navigation. Accurate and up-to-date hydrographic data are essential for ensuring navigational safety, marine resource management, and national maritime security. Indonesia Hydro-Oceanographic Centre (Pushidrosal), as the National Hydrographic Office, is responsible for producing and maintaining nautical charts according to international standards. This study aims to develop strategies to enhance Pushidrosal’s capability in fulfilling hydrographic coverage and meeting the Mandatory IMO Member Audit Scheme (MIMSAS). Using a qualitative descriptive approach supported by GIS-based scoring and SWOT analysis, this research identifies national hydrographic data coverage gaps and proposes prioritized survey strategies. The results show that a systematic and data-driven prioritization of survey areas is critical for achieving compliance with international obligations under SOLAS and UNCLOS. The study provides practical recommendations for Pushidrosal’s strategic planning to accelerate hydrographic data acquisition.